Mapping patterns of co-innovation networks - Urze, Paula (2019)
In recent decades a significant research effort has focused on the role of innovation in giving enterprises a competitive advantage, and of socio-economic growth in general. Using the debate about systems as frameworks for innovation and the mapping of stages of innovation as our starting point, this paper aims to introduce an approach to understand the role of different types of co-innovation networks in terms of their capacity to generate novelty in terms of processes and products. The paper's empirical section is based on one case study about Portugal's largest highway concessionaire.